Evaluation of the Benefits of Senior High School Physical Education: Focus on the values of Friendship, Happiness, and Fitness - Muhammad Fajrul Auliya; Sakban Rosidi; Mukarom Mukarom; Afif Rusdiawan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Physical Education lessons aim to develop fitness (Fit). However, a national survey conducted in Indonesia showed that students' physical fitness level was deficient, as indicated by the less category of 45.97%, very less 10.71%, moderate 37.66%, and good 5.66%. This type of research is gap evaluation research because it compares the observed values with the established standard benchmarks in this study. The subjects of this study were all high school, vocational, and MA students in Indonesia, with a total of 1712 respondents. This research was conducted by distributing questionnaires via the Google form which consisted of 3 questionnaires, namely Sports for Fitness to measure fitness, Sports for Fun questionnaire to measure the joy of exercising and Sports for Interpersonal Peacefulness questionnaire to measure the value of friendship. Data analysis used descriptive test, categorization, and correlation test. The results showed that the average value of physical fitness was 37 with a feasibility value of 40.9, the average joy of exercising was 75.97 with a feasibility value of 65, the average friendship value was 65.31 with a feasibility value of 61. The correlation test showed p value (sig) = 0.000, which means there is a relationship between physical fitness, the joy of exercising and interpersonal peace among high school students in Indonesia. The conclusion that can be drawn is that the average physical fitness is below the eligibility criteria set, the excitement, friendship of students at the senior secondary education level in Indonesia is above the eligibility criteria set.